Geocaching: Interactive Communication Instruments Around the Game - Ihamäki, Pirita Johanna (Eludamos: Journal for Computer Game Culture, 2011)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] --> This article presents a study of geocaching, a mobile outdoor game, and explores the interactive communication instruments players use. In this case study, an interaction communication instrument refers to all the means by which players communicate with each other, including devices and services related to the game. This case study was carried out as an Internet survey with 21 geocachers. The study also discusses articles, which offer more of an informative picture of the global game of geocaching, several related applications, communication channels used by players, and new services around the game. Digital communication channels bring about new varieties of communities, which connect desktop computers to pervasive global networks. Some of these are extensions of non-digital forms of play, while others offer entirely new experiences and playscapes. There are about 3 million people worldwide participating in the game world. Geocaching is a game made by the players, who use GPS technology in a new way, develop it continuously, and create more interactive communication channels and services; it can thus be seen as a pilot test area for game designers and developers. This study will introduce the concept of geocaching and present and define the interaction communication instruments used therein. In the discussion, main conclusions are given in relation to different geocaching approaches and suggestions for future work are outlined.